The physics of the interstellar medium - Dyson, J. E. (John Edward), 1941-; Williams, David A., 1937- (Boca Raton, FL : CRC Press, 2021)
This third edition of The Physics of the Interstellar Medium continues to introduce advanced undergraduates to the fundamental processes and the wide range of disciplines needed to understand observations of the interstellar medium and its role in the Milky Way galaxy. The book is suitable for undergraduate students studying physics, astronomy, and astrophysics. The book also provides concise and straightforward discussions of interstellar physics and chemistry that are useful for more experienced readers. The book leads readers through the range of physical processes operating on both large and small scales that occur in the interstellar medium. It explores the relationship between the dusty, tenuous gas in interstellar space and the formation of stars and planets. This new edition also describes exciting developments in the field of astrochemistry and its interaction with interstellar physics, and the roles played by interstellar dust grains in interstellar physics and chemistry. Simple models in each chapter, together with problems at the end of each chapter, encompass interdisciplinary applications in atomic, molecular, solid state, and surface physics, and gas dynamics. This popular textbook provides a useful overview and grounding in the study of the interstellar medium and brings insight into many aspects of physics. Features An authoritative textbook in the field at this academic level Provides a wide introduction to the interstellar medium whilst remaining accessible and concise Revised throughout, presenting a modern understanding of the interstellar medium
OCLC-licensed vendor bibliographic record.
Keywords: Interstellar matter; SCIENCE / Astronomy; SCIENCE / Astrophysics & Space Science; SCIENCE / Earth Sciences / General